Stamps on terra sigillata found in excavations of the Theatre of Aptera, Crete - Bowsky, Martha W. Baldwin (Archaeopress Roman archaeology, 2019)
Aptera yields more stamped fragments of terra sigillata than any other Cretan city, including Knossos. This book presents stamped fragments of Italian and eastern sigillata found in excavations of the Theatre of Aptera and examines Crete's strategic position amid crossroads of transit and exchange as well as integration into the Roman economy.